Efficacy and safety of novel multiple-chain DAP-CAR-T cells targeting mesothelin in ovarian cancer and mesothelioma: a single-arm, open-label and first-in-human study - Tongpeng Xu; Tian Tian; Chen Wang; Xiaofeng Chen; Xiangrong Zuo; Hanyu Zhou; Jianan Bai; Chenhui Zhao; Sujie Fu; Chongqi Sun; Ting Wang; Ling Zhu; et al. (Genome Medicine)
Abstract Background Despite remarkable achievements in applying chimeric antigen receptor (CAR)-T cells to treat hematological malignancies, they remain much less effective against solid tumors, facing several challenges affecting their clinical use. We previously showed that multichain DNAX-activating protein (DAP) CAR structures could enhance the safety and efficacy of CAR-T cells when used against solid tumors. In particular, mesothelin (MSLN)-targeted CAR-T cell therapy has therapeutic potential in MSLN-positive solid tumors, including ovarian cancer and mesothelioma. Methods In vitro cell killing assays and xenograft model were utilized to determine the anti-tumor efficacy of MSLN targeting DAP-CAR-T cells and other CAR-T cells. ELISA and flow cytometry analysis were used to assess the cytokine secretion capacity and proliferation ability. Eight patients with MSLN expression were enrolled to evaluate the safety and efficacy of MSLN-DAP CAR-T cell therapy. Single-cell sequencing was performed to explore the dynamics of immune cells in patients during treatment and to identify the transcriptomic signatures associated with efficacy and toxicity. Results We found that multichain DAP-CAR formed by combining a natural killer cell immunoglobulin-like receptor truncator and DAP12 exhibited better cytotoxicity and tumor-killing capacity than other natural killer cell-activated receptors associated with DAP12, DAP10, or CD3Z. The safety and efficacy of MSLN-DAP CAR-T cell therapy in patients with ovarian cancer and mesothelioma were evaluated in a single-arm, open-label clinical trial (ChiCTR2100046544); two patients achieved partial response, while four patients had a stable disease status. Furthermore, single-cell sequencing analysis indicated that KT032 CAR-T cell infusion could recruit more immune cells and temporarily remodel the TME. Conclusions Our study highlights the safety and therapeutic efficacy of multiple-chain DAP-CAR-T cell therapy targeting MSLN to treat patients with ovarian cancer and mesothelioma. Trial registration ChiCTR.org.cn, ChiCTR2100046544 . May 21, 2021.